KARTU AKSES SOSIAL: IMAJI DIRI DALAM PRAKTIK SELFIE REMAJA - Eka, Scarletina Vidyayani (Studi Budaya Nusantara, 2023)
Instagram is a medium for sharing images which is used by a large number of users in Indonesia. Viewed from a cultural perspective, filters are a driving force in the mechanism of social relations in the Instagram application. Teenagers and young adults use filters in the objects of their posts as an effort to create images in cyberspace. This artificial engineering helps teenage users to construct a perfect image according to the standards of their social circle. Related to the many variations of filters that can be used on Instagram, this study wants to map the types of filters used by teenagers in their uploaded selfies on Instagram. This field research was conducted to obtain qualitative data regarding the use of filters in selfie uploads involving two groups of adolescents aged 12- 13 years and adolescents aged 14-15 years. The data were taken through FGD with two groups of informants separately so that the data obtained were complete, accurate, and objective. The results of the study show that the dominant use of filters are in the categories: (1) aesthetic, (2) Asian, (3) animation. The filters function to maintain relation within the circle and also to provide access to another circle , as well as to provide a mediation for them to interact among the teenagers.